Dasatinib treatment long-term results among imatinib-resistant/intolerant patients with chronic phase chronic myeloid leukemia are favorable in daily clinical practice - Zackova, Daniela; Klamova, Hana; Belohlavkova, Petra; Stejskal, Lukas; Necasova, Tereza; Semerad, Lukas; Weinbergerova, Barbora; Srbova, Dana; Voglova, Jaroslava; Cicatkova, Petra; Sustkova, Zuzana; Hornak, Tomas; et al. (Leukemia & lymphoma, 2021)
To evaluate long-term real-life results of dasatinib therapy among chronic phase chronic myeloid leukemia patients resistant or intolerant to imatinib, we retrospectively analyzed data of 118 patients treated in centers participating in the database INFINITY. With median follow-up of 37 months, estimated 5-year cumulative incidences of complete cytogenetic and major molecular responses were 78% and 68%, respectively. The estimated 5-year probability of overall survival (OS) and event-free survival (EFS) were 86% and 83%, respectively. Both OS and EFS were significantly improved among patients with BCR-ABL1 transcript level ≤10% at 3 months. Dasatinib toxicity was tolerable however persistent in almost half our patients, even after years of therapy. Pleural effusion occurred in 29% of patients and was responsible for 30% of dasatinib discontinuations. Our results confirmed very good efficacy and acceptable toxicity of dasatinib in second line setting and support the evidence and importance of high-quality real-life CML patient management.
Keywords: Dasatinib; daily clinical practice; inhibitory proteinkinas; výsledek terapie; second line; Leukemia, Myeloid, Chronic-Phase; lidé; chronická myeloidní leukemie; chronická fáze myeloidní leukemie; chronic phase; dasatinib; Treatment Outcome; imatinib; retrospektivní studie; imatinib mesylát; Protein Kinase Inhibitors; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Chronic myeloid leukemia; Retrospective Studies; Imatinib Mesylate; Humans